The benzodiazepine receptor partial agonist Ro 19-8022 suppresses generalized seizures without impairing motor functions in developing rats - Kubová, H; Mikulecká, A; Haugvicová, R; Mares, P (Naunyn-Schmiedeberg's archives of pharmacology, 1999)
The action of a partial benzodiazepine receptor agonist Ro 19-8022 [(R)-1-[(10-chloro-4-oxo-3-phenyl-4H-benzo[a]quinolizin-1-yl)carbo nyl] -2-pyrrolidine-methanol] in doses from 0.01 to 150 mg/kg was studied using motor seizures induced by pentylenetetrazol (PTZ) in rats 7, 12, 18, 25 and 90 days old. Generalized tonic-clonic seizures were suppressed in all age groups, the three youngest groups being more sensitive than older animals. The highest dose of Ro 19-8022 did not exhibit anticonvulsant action in the 25-day-old rats. The other types of seizures (minimal clonic) induced by PTZ were suppressed by Ro 19-8022 only in 18-day-old and older rats in which PTZ reliably elicited these types of seizures. The doses of 50, 100 and 150 mg/kg were ineffective against minimal seizures. On the contrary, incidence of minimal seizures was significantly increased by Ro 19-8022 in 7-and 12-day-old rat pups. Motor performance of rat pups was not compromised by Ro 19-8022 (0.5 and 50 mg/kg) in contrast to the full agonist midazolam (1 and/or 2 mg/kg). The duration of anticonvulsant effects studied with a dose of 0.5 mg/kg was longer in 12-day-old than in adult rats. This dose of Ro 19-8022 resulted in a rebound proconvulsant effect 24 and 48 h after the administration in 12-day-old rats only. Ro 19-8022 exhibited an excellent anticonvulsant action especially against generalized tonic-clonic seizures; this action was lost with very high doses. It did not compromise the motor system, but in some tests motivation was probably lost.
Keywords: chinoliziny; Dose-Response Relationship, Drug; záchvaty; Aging; vztah mezi dávkou a účinkem léčiva; Pentylenetetrazole; Rats; antagonisté receptorů GABA-A; Time Factors; konvulziva; antikonvulziva; Rats, Wistar; mužské pohlaví; Quinolizines; Seizures; krysa rodu Rattus; Motor Skills; motorické dovednosti; pyrrolidiny; stárnutí; Pyrrolidines; zvířata; Anticonvulsants; Midazolam; časové faktory; potkani Wistar; pentylentetrazol; Convulsants; midazolam; GABA-A Receptor Antagonists; Male; Animals